Assessing a startup opportunity in Colombia´s payment gateway sector - Morales, Jose Ignacio Caballero (2021)
This research was done in order to develop strategies for assessing an opportunity in the payment gateway sector. Developing it, different trends were found and a problem big enough about the displeasure of customer when queuing to pay in the retail sector, creating a mix of problems addressed with strategies and technology development, based on an international benchmark in the sector, that would allow us to enter this profitable industry in Colombia.